2021
DOI: 10.1039/d1cp01443a
|View full text |Cite
|
Sign up to set email alerts
|

X-ray stability and degradation mechanism of lead halide perovskites and lead halides

Abstract: Lead halide perovskites have become a leading material in the field of emerging photovoltaics and optoelectronics. Significant progress has been achieved in improving the intrinsic properties and environmental stability of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 53 publications
2
60
1
Order By: Relevance
“…Therefore, such high carrier concentrations can promote degradation of the perovskite in ways distinct from those encountered under illumination at 1 sun (10 14 to 10 16 carriers cm -3 , mostly generated at band edge), likely aiding in the radiolysis of the organic cations in the perovskite. [50] The radiation hardness described here suggests good resilience of these materials to degradation from electron radiation in space. Assuming radiation damage of hybrid perovskite being dependent on the total dose rather than on the dose rate, [11,12] the critical fluence for electrons would be accumulated after around ≈2000 years in the Earth orbit or ≈200 years at harsher orbits like Jupiter (see Figure S21, Supporting Information).…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…Therefore, such high carrier concentrations can promote degradation of the perovskite in ways distinct from those encountered under illumination at 1 sun (10 14 to 10 16 carriers cm -3 , mostly generated at band edge), likely aiding in the radiolysis of the organic cations in the perovskite. [50] The radiation hardness described here suggests good resilience of these materials to degradation from electron radiation in space. Assuming radiation damage of hybrid perovskite being dependent on the total dose rather than on the dose rate, [11,12] the critical fluence for electrons would be accumulated after around ≈2000 years in the Earth orbit or ≈200 years at harsher orbits like Jupiter (see Figure S21, Supporting Information).…”
Section: Resultsmentioning
confidence: 71%
“…In fact, the presence of the organic cation species at the A position has been proposed to trigger degradation processes toward PbI 2 as opposed to the Pb 0 , mostly only seen from inorganic compositions, as the organics can undergo radiolysis more easily than the Pb 2+ cation upon electron and X‐ray illumination. [ 22,50 ] Future work should focus on combining the microscopy techniques used here with the passivation strategies that have been successfully employed in halide perovskite semiconductors (passivation by coordinate bonding, ionic bonding, or chemical conversion), [ 51 ] to gain better understanding of the chemistry of passivation in hybrid halide perovskites. In fact, SED was recently used to understand the effect of surface‐bound passivation agents on the crystallinity of halide perovskites by means of octahedral tilting stabilization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies using x-ray diffraction on thin films and synchrotron x-ray powder diffraction showed conflicting results on whether CH 3 NH 3 Pb(I 1-x Br x ) 3 exhibits full miscibility or not [27]. While the conflicting evidence may be related to the different excitation intensity of the light source [28], the question of whether these systems exhibit full miscibility in the dark at room temperature is still open. The additional uncertainty on the structural reversibility of these systems upon photo de-mixing and dark re-mixing complicates the matter.…”
Section: Photo De-mixing In Mixed Halide Perovskitesmentioning
confidence: 99%
“…Exposure to intense X-rays typically accelerates the decomposition of hybrid perovskites into Pb(0), I 2 , and organic degradation products. [51,52] This decomposition is characterized by a general but not immediate decrease of the overall intensity as well as broadening of the perovskite Bragg peaks. Stuckelberger et al have shown that the interaction of MAPbI 3 with 8 keV photons induces ionic diffusion, [53] which is most probably at the origin of the observed degradation upon increasing the radiation dose.…”
Section: Texture In Mapbi 3 Thin Layersmentioning
confidence: 99%